2021
DOI: 10.3892/ol.2021.12647
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑217 inhibits the proliferation and invasion, and promotes apoptosis of non‑small cell lung cancer cells by targeting sirtuin 1

Abstract: Non-small cell lung cancer (NSCLC) is a common malignancy worldwide. MicroRNA (miR)-217 and sirtuin 1 (SIRT1) have been reported to play significant roles in different types of cancer, such as osteosarcoma and prostate cancer; however, the association between miR-217 and SIRT1 in the cell proliferation, apoptosis and invasion of NSCLC remain unknown. Thus, the present study aimed to investigate the roles of miR-217 and SIRT1 in NSCLC. The expression levels of miR-217 and SIRT1 were detected via reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…371 In non-small cell LC (NSCLC), the SIRT1-mediated AMPK/mTOR signaling pathway could promote A549 and H1299 cell proliferation, invasion and apoptosis. 372 Expression of SIRT1 can be regulated by ncRNAs, which further influence its effects in regulating cell migration and invasion. For instance, in colorectal cancer (CRC) cells, downregulation of SIRT1, by miR-34a transfection, increases the level of acetylated-p53 and inhibits cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…371 In non-small cell LC (NSCLC), the SIRT1-mediated AMPK/mTOR signaling pathway could promote A549 and H1299 cell proliferation, invasion and apoptosis. 372 Expression of SIRT1 can be regulated by ncRNAs, which further influence its effects in regulating cell migration and invasion. For instance, in colorectal cancer (CRC) cells, downregulation of SIRT1, by miR-34a transfection, increases the level of acetylated-p53 and inhibits cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“… 371 In non-small cell LC (NSCLC), the SIRT1-mediated AMPK/mTOR signaling pathway could promote A549 and H1299 cell proliferation, invasion and apoptosis. 372 …”
Section: Introductionmentioning
confidence: 99%
“…133 microRNA-217 mimetic inhibited cell proliferation and invasion, promoted apoptosis, and activated AMPK/mTOR in H1299 and A549 cell cultures. 167 Paris saponin VII (PSVII), extracted from Trillium tschonoskii maxim, could inhibit cell viability and colony formation of H460 and PC9 cell cultures, induce apoptosis and autophagy by activating AMPK directly, as also downregulate p-mTOR, p-S6K1, p-4EBP1. 156 Polyphyllin I, extracted from Paris polyphylla, inhibited cell viability and colony formation, induced apoptosis and autophagy through AMPK/mTOR in PC9, H460, and 95D cell cultures, inhibited tumor growth and upregulated the p-AMPK level and LC3 II protein level in the lung tissue of mice.…”
Section: The Activation Of Ampk Can Inhibit Mmp-2/9 and Activate Foxo3αmentioning
confidence: 99%
“…Studies have confirmed that multiple miRNAs can target NUSAP1 acting as an upstream regulators in various malignant tumors except glioma, such as miR-193a-5p [ 6 ], miR-758-3p [ 20 ], miR-569 [ 21 ], and miR-769-5p [ 22 ]. Here, we conducted bioinformatic analysis of TCGA LGG-GBM cohort and ENCORI database and screened that a novel lncRNA LINC01393 which may serve as a sponge for miR-128-3p in the regulation of NUSAP1 expression.…”
Section: Introductionmentioning
confidence: 99%